Fluctuations of the Intraocular Pressure in One Eye Influence the Intraocular Pressure in the Fellow Eye. (1st February 2017) - Voykov, Bogomil; Blumenstock, Gunnar; Ziemssen, Focke; Bartz-Schmidt, Karl Ulrich; Schultheiss, Maximillian
ABSTRACT: Purpose : To investigate the ophthalmotonic consensual reaction (OCR) in healthy individuals. Methods : This was a cohort study of 59 pairs of eyes of patients who underwent cataract surgery in one eye and had no other ocular pathology than cataract. Main outcome measure was change of intraocular pressure (IOP) in the untreated fellow eye. The IOP was measured 1 hour before, 1 hour after, and 1 day after surgery. Results : One hour after surgery, IOP decreased in 24 (41%) operated eyes (group A). In the corresponding untreated fellow eyes (group Af), the mean IOP (±standard deviation [SD]) did not change (14.1 ± 3.0 mmHg preoperatively to 14.2 ± 3.1 mmHg postoperatively, p = 0.8). Only two operated eyes showed unchanged IOP (group B). In 33 (56%) operated eyes, the IOP increased (group C). In the untreated fellow eyes (group Cf), the mean IOP decreased significantly from 15.1 ± 2.9 to 13.7 ± 2.6 mmHg ( p = 0.0012). One day after surgery, the mean IOP of group Af decreased significantly from 14.2 ± 3.1 (postoperative IOP) to 12.7 ± 3.2 mmHg ( p = 0.007). In group Cf, the mean IOP revealed no changes from 13.7 ± 2.6 to 13.5 ± 2.4 mmHg ( p = 0.69). Conclusions : Our results showed some evidence for the existence of the OCR in healthy individuals. Significant IOP elevation in one eye resulted in IOP reduction in the fellow eye. Interestingly, this phenomenon did not exist vice versa.